2014
DOI: 10.3389/fncel.2014.00248
|View full text |Cite
|
Sign up to set email alerts
|

In vivo overexpression of X-linked inhibitor of apoptosis protein protects against neomycin-induced hair cell loss in the apical turn of the cochlea during the ototoxic-sensitive period

Abstract: Aminoglycoside-induced cochlear ototoxicity causes hair cell (HC) loss and results in hearing impairment in patients. Previous studies have developed the concept of an ototoxicity-sensitive period during which the cochleae of young mice are more vulnerable to auditory trauma than adults. Here, we compared neomycin-induced ototoxicity at the following four developmental ages in mice: postnatal day (P)1–P7, P8–P14, P15–P21, and P60–P66. We found that when neomycin was administered between P8 and P14, the auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…6a,c). Previous studies have reported that cleaved caspase-3 and TUNEL can be used as markers of apoptosis in aminoglycoside-induced HC death303233343536. To confirm our findings, we performed active caspase-3 and TUNEL staining to detect the apoptotic HEI-OC1 cells.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…6a,c). Previous studies have reported that cleaved caspase-3 and TUNEL can be used as markers of apoptosis in aminoglycoside-induced HC death303233343536. To confirm our findings, we performed active caspase-3 and TUNEL staining to detect the apoptotic HEI-OC1 cells.…”
Section: Resultssupporting
confidence: 77%
“…To determine whether the c-Myb expression in cochlear HCs was affected by neomycin treatment, C57BL/6 mice were given daily subcutaneous injections of neomycin (200 mg/kg) from P7 to P14, which is the ototoxic-sensitive period in the cochlea32. Mice in the control group were given sterile saline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ototoxic drugs cause hearing loss by inducing HC apoptosis, primarily by altering the MMP of the mitochondria ( Huang et al, 2000 ; Wu et al, 2002 ; Sun et al, 2015 ; Guan et al, 2016 ; He et al, 2016 ; Yu et al, 2017 ). Mitochondria play an important role in cell metabolism, and aminoglycoside-induced apoptosis is closely related to mitochondrial dysfunction, which leads to decreased MMP and increased ROS ( Joza et al, 2001 ; Chipuk et al, 2004 ; Coffin et al, 2013 ; Sun et al, 2014 , 2015 ; Mei et al, 2015 ). The accumulation of ROS in the mitochondria is an important trigger of apoptosis, and it has been reported that ROS play an important role in noise-induced and ototoxic drug-induced HC damage and hearing loss ( Sun et al, 2014 , 2015 ; Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to investigate the molecular mechanism behind aminoglycoside-induced auditory sensory cell damage and to seek effective drugs for preventing and treating aminoglycoside-induced deafness. Several studies have suggested that aminoglycosides induce intrinsic apoptosis of HCs through oxidative stress ( Mangiardi et al, 2004 ; Coffin et al, 2013 ; Sun et al, 2014 , 2015 ; Liu et al, 2016 ), while others have reported that the accumulation of reactive oxygen species (ROS) plays an important role in the death of HCs ( Clerici et al, 1996 ; Choung et al, 2009 ). ROS can be cleared by physiological cellular processes; however, they are harmful when their concentration exceeds the cell’s capacity to remove them ( He et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%